The Degree of Association of Risk Factors in A Population With High Blood Pressure and Various Levels of Cardiovascular Risk - Madina Yunusovna, Valieva; Zukhriddin Salokhiddinovich, Salokhiddinov; Yorkinoy Mirzaxamdamovna, Niyazova; Gavxar Tulkinovna, Abduvalieva; Dono Kamalovna, Maksumova; Nafisa Xaydaralievna, Yaminova; Dilshodbek Abduqaxorovich, Qodirov; Sherzodbek Ozodbekovich, Alibekov; Adaxam Alisherovich, Abdusattarov; Shoxabbos Nozimjon ugli, Salomov (Journal of Neonatal Surgery, 2025)
The presence of 22 behavioral risk factors elevates the detection of high blood pressure by over 9.5 times. Complications such as left ventricular hypertrophy (85.3%), cerebrovascular diseases (90.9%), myocardial infarction (80.0%), heart failure (87.5%), symptomatic peripheral artery damage (66.7%), and diabetes mellitus (75.0%) significantly influence the prognosis of total cardiovascular risk alongside hypertension.